Current and future sinkhole susceptibility in karst and pseudokarst areas of the conterminous United States - Wood, Nathan J.; Doctor, Daniel H.; Alder, Jay; Jones, Jeanne (Frontiers in Earth Science, 2023)
Sinkholes in karst and pseudokarst regions threaten infrastructure, property, and lives. We mapped closed depressions in karst and pseudokarst regions of the conterminous United States (U.S.) from 10-meter-resolution elevation data using high-performance computing, and then created a heuristic additive model of sinkhole susceptibility that also included nationally consistent data for factors related to geology, soils, precipitation extremes, and development. Maps identify potential sinkhole hotspots based on current conditions and projections for 50 years into the future (the years 2070-2079) based on climate change and urban development scenarios. Areas characterized as having either high or very high sinkhole susceptibility contain 94-99% of known or probable sinkhole locations from three U.S. state databases. States and counties with the highest amounts and percentages of land in zones of highest sinkhole susceptibility are identified. Projected changes in extreme precipitation and development did not substantially change current hotspots of highest sinkhole susceptibility. Results provide a uniform index of sinkhole potential that can support national planning, instead of existing assessments produced through various methods within individual states or smaller areas.